Before and after the Hartz reforms: The performance of active labour market policy in Germany - Lena Jacobi; Jochen Kluve (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2007)
Having faced high unemployment rates for more than a decade, the German government implemented a comprehensive set of labour market reforms during the period 2003-2005. This paper describes the economic and institutional context of the German labour market before and after these so-called Hartz reforms. Focussing on active policy measures, we delineate the rationale for reform and its main principles. As preliminary results of programme evaluation studies post-reform have become available just now, we give a first assessment of the effectiveness of key elements of German active labour market policy before and after the Hartz reforms. The evidence indicates that the re-organisation of public employment services was mainly successful, with the exception of the outsourcing of services. Re-designing training programmes seems to have improved their effectiveness, while job creation schemes continue to be detrimental for participants' employment prospects. Wage subsidies and start-up subsidies show significantly positive effects. On balance, therefore, the reform seems to be moving the German labour market in the right direction.
Keywords: 330; Arbeitsmarktpolitik - Erfolgskontrolle; Hartz-Reform; Bundesagentur für Arbeit - Organisation; Weiterbildungsförderung; Arbeitsbeschaffungsmaßnahme; aktivierende Arbeitsmarktpolitik; Deregulierung; Lohnsubvention; Existenzgründungszuschuss